Environmental sustainability and product portfolio management in biodiversity firms: A comparative analysis between Portugal and Brazil - Jugend, Daniel [UNESP]; Figueiredo, José; Pinheiro, Marco Antonio Paula [UNESP] (My University, 2017)
Although relevant research on environmental sustainability or product portfolio management is quite developed, few studies integrate the two areas. This research aims to shed light on the environmental sustainability practices adopted in product portfolio through a cross-country case study on leading biodiversity companies located in Portugal and Brazil. The results demonstrate that the pressure of government regulation and the tendency of markets to demand consumer products that do not harm biodiversity have changed the mindset of biodiversity companies, which have been trying to expand their environmentally sustainable product portfolio (ESPP). The results also indicate that tuning ESPP improves market performance and that the main barriers to integrate environmental sustainability into the product portfolio are technological.
Keywords: Biodiversity companies; Environmental sustainability; New product development; Product portfolio management